2005
DOI: 10.1002/jcp.20489
|View full text |Cite
|
Sign up to set email alerts
|

The epigenetic network regulating muscle development and regeneration

Abstract: This review focuses on our current knowledge of the epigenetic changes regulating gene expression at the chromatin and DNA level, independently on the primary DNA sequence, to reprogram the nuclei of muscle precursors during developmental myogenesis and muscle regeneration. These epigenetic marks provide the blueprint by which the extra-cellular cues are interpreted at the nuclear level by the transcription machinery to select the repertoire of tissue-specific genes to be expressed. The reversibility of some o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
97
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(101 citation statements)
references
References 198 publications
3
97
0
Order By: Relevance
“…Data obtained with SB203580 were in line with data in Figure 3A and with the notion that p38 MAPK needs to be activated for myoblasts to differentiate 15,17,18 and indicated that expression of RAGE in TE671 cells was sufficient to restore a crucial event in myogenic differentiation, ie, sustained p38 MAPK activation. By contrast, inhibition of mitogenactivated protein kinase kinase-ERK1/2 favored the execution of the myogenic program activated by RAGE engagement in TE671/RAGE cells ( Figure 3E) in accordance with the notion that ERK1/2 inactivation results in enhanced myoblast differentiation.…”
Section: Rage Engagement By Hmgb1 In Te671/rage Cells Activates the Psupporting
confidence: 85%
See 2 more Smart Citations
“…Data obtained with SB203580 were in line with data in Figure 3A and with the notion that p38 MAPK needs to be activated for myoblasts to differentiate 15,17,18 and indicated that expression of RAGE in TE671 cells was sufficient to restore a crucial event in myogenic differentiation, ie, sustained p38 MAPK activation. By contrast, inhibition of mitogenactivated protein kinase kinase-ERK1/2 favored the execution of the myogenic program activated by RAGE engagement in TE671/RAGE cells ( Figure 3E) in accordance with the notion that ERK1/2 inactivation results in enhanced myoblast differentiation.…”
Section: Rage Engagement By Hmgb1 In Te671/rage Cells Activates the Psupporting
confidence: 85%
“…We found that TE671 cells do not express RAGE, myogenin, or MHC; proliferate at a high rate; and are unable to complete the myoblast differentiation pro- p38 MAPK activity is crucial for activation of the myogenic program in myoblasts and RMS cells, and Akt is also required for myoblast differentiation and myoblast/ myotube hypertrophy. 15,17,18,32 TE671/RAGE cells show increased extents of phosphorylation (activation) of the promyogenic p38 MAPK and Akt, and HMGB1 further increases them. Thus, a relationship exists in TE671/ RAGE cells among RAGE expression, p38 MAPK and Akt activation, up-regulation of myogenin and MHC expression, induction of MCK, and cell hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This hypothesis is consistent with mechanism of action of the DNA demethylating agent, 5-azacytidine, which has been used to induce cardiomyogenic gene expression in Sca-1 + cardiovascular progenitors [32] and human ESCs [26]. Moreover, DNA demethylation has been implicated in the epigenetic regulation of skeletal muscle specification [33,34]. While a number of significant challenges remain, the findings here suggest that the reprogramming of human VMs to human ViPSCs may be a tractable strategy of deriving large numbers of VMs for cardiac regenerative medicine.…”
Section: Discussionsupporting
confidence: 74%
“…In recent years, it has been demonstrated that precise control of the chromatin structure of specific genes is crucial for the maintenance of the pluripotency of the inner cell mass (Boyer et al, 2006), while remodeling of chromatin is crucial for the commitment of these cells to specific lineages during development (Kondo, 2006), and their final terminal differentiation (Ehrlich, 2003;Hsieh and Gage, 2004;Palacios and Puri, 2006;Wilson et al, 2005;Zhou et al, 2005). The molecular mechanisms controlling the chromatin structure of genes has been under intense investigation and has been found to result from numerous epigenetic modifications including the differential regulation of histone acetylation, methylation and phosphorylation, DNA methylation and the use of histone variants in the nucleosomal structure (Wegel and Shaw, 2005).…”
Section: Resultsmentioning
confidence: 99%